Tragedi Kanjuruhan di Berita Online: Analisis Wacana Kritis Model Michel Foucault - Maftuhah Salamatun Ni'mah; Ahmad Diny Hidayatullah; Masrokhin Masrokhin (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
The Kanjuruhan tragedy was a major disaster that occurred in Indonesia, and this event was able to attract the attention of foreign news, as evidenced by the fact that several foreign platforms also reported on it. it can really understand the meaning. This research aims to determine the relationship and power of online news portals and the impacts that occur. This research is a qualitative descriptive research with a data analysis model using electronic media analysis consisting of media space, media archives, media objects and experiences. The primary data source is the Kanjuruhan tragedy news text from the BBC Arabic, CNN Arabic and Al Jazeera portals. The secondary data source is the use of literature related to Michel Foucault's critical discourse. The results of the research are the relations of power and knowledge that occur, including the police, FIFA, society, law, football teams, government authorities, and PSSI. The impact of knowledge and power relations resulted in legal authorities taking action to punish football officials responsible for the Kanjuruhan tragedy, regulations regarding FIFA prohibiting the use of tear gas, which were violated, caused FIFA to distrust the police, the police is in the spotlight public because using authority is not according to norms. Keywords: Cyber Media, Michel Foucault's Critical Discourse, Online News Portal,  Power and Knowledge Relations, The Kanjuruhan Tragedy